The Essence of the Company’s Intellectual Holdings and their Evaluation Indicators - M. V. Apanasevich (Цифровая трансформация)
Intellectualization of the modern economy is an objective process, which is naturally predetermined by the new quality of the role and place of a man in the system of economic relations. The transformation of a human being into simultaneously an objective, a mean, and a condition of economic activity obliges us to characterize the processes of individual and social reproduction in a new way. The trends of modern economic development are reflected in such concepts as intellectual resources, intellectual capital of a company. At the moment, despite the abundance of literature, there is no single generally accepted approach to the definition and evaluation of these economic categories. The article presents the approaches of various authors to the interpretation of the term “intellectual capital”. As a result of this research, the author’s designation of the company’s intellectual resources – intellectual holdings, their structure and evaluation methods are proposed.